Willie and His Make-Up,' Puck Magazine caricature, 1906 (Keppler & Schwarzmann, 1906)
Issue of 'Puck' (volume LX (volume 60), no. 1545) humor magazine featuring a caricature of William Randolph Hearst dressed in the clothes of preceding Presidents Washington, Lincoln, Jefferson, and Jackson while Arthur Brisbane observes from the background. The illustration is titled "Willie and His Make-Up." and the text reads ""We will succeed if we walk straightly along the path where Washington and Jefferson and Jackson and Lincoln have walked before us."" The back features one-liners, anecdotes, and a comic of William Bourke Cockran dressed as Uncle Sam and William Randolph Hearst sporting a "Hoist" tag with text below reading ""He's bad enough for me."" Circa October 10th, 1906.